The implementation of guided inquiry learning model to improve students’ science process skills in physics subject - Barus, Carolina Sri Athena; Sopacua, Venty (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2025)
Science process skills are a fundamental component of physics education, as the discipline is inherently inseparable from the application of scientific procedures. This study aimed to describe the improvement of students’ science process skills through the implementation of a guided inquiry learning model in physics instruction. A mixed-methods approach, combining qualitative and quantitative perspectives with descriptive analysis, was employed. The participants consisted of 29 students from grade XI Science-5 at Senior High School A in Ambon City. Data collection utilized both test and non-test instruments. The test instrument comprised 15 items designed to measure indicators of science process skills within the topic of material elasticity, while the non-test instrument was a questionnaire administered to evaluate students’ learning activities. Data analysis incorporated both quantitative and qualitative data, focusing on the comparison of science process skills before (pretest) and after (posttest) the intervention, complemented by learning activity assessments. The N-Gain analysis revealed a statistically significant improvement between pretest and posttest scores: 20.7% of students were categorized as high, 69% as moderate, and 10.3% as low. Learning activities related to identifying variables, formulating problems, developing hypotheses, and designing experiments were classified as active to highly active, while interpreting data was rated as moderately active. These findings demonstrate that the guided inquiry model effectively enhances science process skills in physics education.